1987
DOI: 10.1111/j.1476-5381.1987.tb11299.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitroglycerin on exercise‐induced regional myocardial contractile dysfunction are not diminished by pretreatment with dihydroergotamine

Abstract: Because controversy exists regarding the effects of dihydroergotamine (DHE) on the performance of underperfused myocardium, the effects of DHE were investigated in a model of exercise‐induced regional myocardial dysfunction in conscious dogs. We also investigated a possible functional antagonism between DHE and nitroglycerin that might reduce the latter drug's antianginal efficacy. Investigations were carried out in conscious dogs. After stenosis of the circumflex branch of the left coronary artery that minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Direct actions on the coronary circulation include dilation of large and small intramural coronary arteries, collateral vessel dilation and replenishment of nitric oxide 30 . As is the case in humans, prior studies have demonstrated an unequivocal and beneficial effect with TNG in various canine models of demand ischaemia 27,28,31–34 . The lack of change in double product with TNG suggests that peak myocardial oxygen consumption remained unchanged while peak exercise capacity was increased by 16%, consistent with the known ability of TNG to reduce myocardial oxygen demand.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Direct actions on the coronary circulation include dilation of large and small intramural coronary arteries, collateral vessel dilation and replenishment of nitric oxide 30 . As is the case in humans, prior studies have demonstrated an unequivocal and beneficial effect with TNG in various canine models of demand ischaemia 27,28,31–34 . The lack of change in double product with TNG suggests that peak myocardial oxygen consumption remained unchanged while peak exercise capacity was increased by 16%, consistent with the known ability of TNG to reduce myocardial oxygen demand.…”
Section: Discussionmentioning
confidence: 70%
“…30 As is the case in humans, prior studies have demonstrated an unequivocal and beneficial effect with TNG in various canine models of demand ischaemia. 27,28,[31][32][33][34] The lack of change in double product with TNG suggests that peak myocardial oxygen consumption remained unchanged while peak exercise capacity was increased by 16%, consistent with the known ability of TNG to reduce myocardial oxygen demand. Increased exercise capacity was accompanied by increased ischaemic zone wall thickening throughout the exercise protocol, with a similar beneficial effect noted in the ischaemic zone ST segment.…”
Section: Figmentioning
confidence: 77%